Palmoplantar lesions: an atypical presentation of dermatitis herpetiformis. - Figueiredo, C.; Calvão, J.; Almeida, S.; Cardoso, J.C.; Ramos, L. (European Journal of Pediatric Dermatology, 2023)
Dermatitis herpetiformis (DH) is a chronic skin condition usually associated with celiac disease (CD), ordinarily manifesting as an intensely pruritic papulovesicular eruption in characteristic sites. In this paper, a case of palmoplantar lesions is described as the only manifestation of DH in a child who did not show gastrointestinal symptoms or diagnostic criteria for CD.